Adaptive Fuzzy Sliding Mode Controller and Observer for a Dive Cell. Issue 1 (21st October 2015) - Bessa, Wallace M.; Kreuzer, Edwin; Krumm, Ludwig; Pick, Marc‐André; Solowjow, Eugen
Abstract We present an adaptive fuzzy sliding mode control strategy in combination with a sliding mode observer for a dive cell. Numerical results demonstrate the outperformance of the presented controller compared to a conventional sliding mode approach. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)